Reconstruction and identification of pairs of collimated $$τ $$ τ -leptons decaying hadronically using $$\sqrt{s}=13$$ s = 13 TeV pp collision data with the ATLAS detector - ATLAS Collaboration (European Physical Journal C: Particles and Fields)
Abstract This paper describes an algorithm for reconstructing and identifying a highly collimated hadronically decaying $$τ $$ τ -lepton pair with low transverse momentum. When two $$τ $$ τ -leptons are highly collimated, their visible decay products might overlap, degrading the reconstruction performance for each of the $$τ $$ τ -leptons. A dedicated treatment attempting to tag the $$τ $$ τ -lepton pair as a single object is required. The reconstruction algorithm is based on a large radius jet and its associated two leading subjets, and the identification uses a boosted decision tree to discriminate between signatures from $$τ ^+τ ^-$$ τ + τ - systems and those arising from QCD jets. The efficiency of the identification algorithm is measured in $$Zγ $$ Z γ events using proton–proton collision data at $$\sqrt{s}=13$$ s = 13 TeV collected by the ATLAS experiment at the Large Hadron Collider between 2015 and 2018, corresponding to an integrated luminosity of $$139\,\text{ fb}^{-1}$$ 139 fb - 1 . The resulting data-to-simulation scale factors are close to unity with uncertainties ranging from 26 to 37%.